Radio-TV Information and Participation: The case of the “delegated decrees” (1969-1975) - Roghi, Vanessa (Rivista di Storia dell’Educazione, 2024)
This essay aims to reconstruct part of the complex story that links the history of broadcasting information to that of political participation in post-World War II Italy. In this perspective, the approval of the “decreti delegati” on schools in 1974 marks an important watershed. It also intends to emphasize how essential the commitment of a part of the broadcasting operators was in making the measures themselves, somehow more comprehensible to the public. But it also intends to highlight how the decrees themselves served as a real accelerator in rethinking some of the dynamics of broadcasting information in the years leading up to the end of the public monopoly.